2021
DOI: 10.3389/fonc.2021.752192
|View full text |Cite
|
Sign up to set email alerts
|

From Biology to Clinical Practice: Iron Chelation Therapy With Deferasirox

Abstract: Iron chelation therapy (ICT) has become a mainstay in heavily transfused hematological patients, with the aim to reduce iron overload (IOL) and prevent organ damage. This therapeutic approach is already widely used in thalassemic patients and in low-risk Myelodysplastic Syndrome (MDS) patients. More recently, ICT has been proposed for high-risk MDS, especially when an allogeneic bone marrow transplantation has been planned. Furthermore, other hematological and hereditary disorders, characterized by considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 117 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…Recent research reported similar ICT safety and efficacy in higher‐risk MDS patients compared to lower‐risk MDS patients 33 . Although this retrospective analysis was performed in a small higher‐risk MDS population, it indicates that monitoring potential iron overload is relevant in this patient group, especially since the life expectancy of higher‐risk MDS patients is improving 9,32,33 . Because it is unclear whether the benefits of ICT outweigh its side‐effects in MDS patients and due to the costs of ICT, treating haematologists seem reluctant in providing ICT in MDS patients 19,21,29 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Recent research reported similar ICT safety and efficacy in higher‐risk MDS patients compared to lower‐risk MDS patients 33 . Although this retrospective analysis was performed in a small higher‐risk MDS population, it indicates that monitoring potential iron overload is relevant in this patient group, especially since the life expectancy of higher‐risk MDS patients is improving 9,32,33 . Because it is unclear whether the benefits of ICT outweigh its side‐effects in MDS patients and due to the costs of ICT, treating haematologists seem reluctant in providing ICT in MDS patients 19,21,29 .…”
Section: Discussionmentioning
confidence: 90%
“…29 It has been described that iron overload is correlated with decreased survival, higher incidence of infections, ineffective erythropoiesis and an increased risk of leukemic transformation of MDS due to genomic alterations. 9,19,[30][31][32] The TEL-ESTO study showed positive clinical effects of ICT in lower-risk MDS patients, and another study noted better overall survival amongst patients who received ICT as recommended by guidelines; better monitoring of potential iron overload might therefore prevent iron overload-related effects that impair patient life expectancy. 9,19,31 In our study population, the decision to initiate ICT was most likely influenced by the clinical performance of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, renal failure and cytopenias have been reported in patients receiving DFX oral suspension tablets [ 48 ]. DFX treatments have shown feasibility and efficacy in patients with thalassemia intermedia [ 49 ], myelofibrosis (MF), myelodysplastic syndrome (MDS) [ 50 , 51 , 52 ], and myeloproliferative neoplasms in fibrotic phase (MPN) [ 53 ]. Due to reports of serious adverse reactions, DFX was discontinued in 2020; however, it is available as a generic drug [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…41 As in other chronic hematological malignancies, iron overload due to red blood cell transfusions has been associated with reduced survival also in MF. 44 Indeed, in the presence of iron overload, there is an abnormal release of reactive oxygen species in the bone marrow, resulting in impaired marrow function. 45 Additionally, a recent Italian study has shown that use of iron chelation therapy (deferasirox) in combination with RUX in anemic MF patients can increase Hb levels and achieve iron chelation responses that are associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%